2015
DOI: 10.1002/2015ja021089
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characteristics of EMIC waves: Van Allen Probe observations

Abstract: Utilizing the data from the magnetometer instrument which is a part of the Electric and Magnetic Field Instrument Suite and Integrated Science instrument suite on board the Van Allen Probe A from September 2012 to April 2014, when the apogee of the satellite has passed all the magnetic local time (MLT) sectors, we obtain the statistical distribution characteristics of electromagnetic ion cyclotron (EMIC) waves in the inner magnetosphere over all magnetic local times from L = 3 to L = 6. Compared with the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 52 publications
7
100
0
Order By: Relevance
“…On the other hand, this study concentrates on the distribution of EMIC waves in the inner magnetosphere in different geomagnetic condition indicated by SYM‐H index. By advantage of 64 Hz magnetic field data from EMFISIS instrument [ Kletzing et al , ] on board Van Allen Probe A, the upper frequency limit of EMIC waves in this study extends to 10 Hz [ Wang et al , ]. Peak occurrences are also found in noon to dusk sector during storm main phase but in the region with L between 5 and 6.5.…”
Section: Summary and Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…On the other hand, this study concentrates on the distribution of EMIC waves in the inner magnetosphere in different geomagnetic condition indicated by SYM‐H index. By advantage of 64 Hz magnetic field data from EMFISIS instrument [ Kletzing et al , ] on board Van Allen Probe A, the upper frequency limit of EMIC waves in this study extends to 10 Hz [ Wang et al , ]. Peak occurrences are also found in noon to dusk sector during storm main phase but in the region with L between 5 and 6.5.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…Furthermore, they identify the location of EMIC waves relative to plasmapause according to empirical models, while plasma density data are shown in this manuscript. Actually, in our previous research [ Wang et al , ], utilizing the plasma density data, majority of EMIC waves observed by Van Allen Probe A were identified inside the plasmasphere. On the other hand, most of oxygen band EMIC waves reported in Yu et al [] were identified in the plasmasphere.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the electron-cyclotron (ELF/VLF) waves and EMIC waves are localized mainly in the dusk and dawn sectors, respectively (e.g., Li et al 2011;Wang et al 2015). Thus, observations of longitudinal distribution of these waves and drifting plasmas are essentially important to understand particle energization and loss in the inner magnetosphere quantitatively.…”
Section: Introductionmentioning
confidence: 99%